Simulasi Monte Carlo dalam Memprediksi Tingkat Lonjakan Penumpang - Mardiati, Dina (Jurnal Informatika Ekonomi Bisnis, 2020)
Tri Arga Travel is a company engaged in transportation services. The company really prioritizes the quality of service to consumers. So that on holidays there is usually a surge in passengers that cannot be predicted by the company. This greatly affects service to passengers. The purpose of this research is to predict the surge rate of PT. Tri Arga Travel, making it easier for the leadership of PT. Tri Arga Travel to take a policy when there is a surge in passengers in the future. The data used in this study is data on the number of passengers in 2017, 2018, and 2019 with the aim of padang-perawang. Then, the data is processed using the Monte Carlo method. The Monte Carlo method is a simulation method that uses random numbers obtained from the Linear Congruential Generator (LCG) to predict the rate of passenger spike in the following year by utilizing the previous year's passenger data. The results obtained from testing the Monte Carlo simulation can be seen that in July it is predicted that there will be a surge in passengers with an average level of accuracy of 86.74%. With a fairly high level of accuracy, the application of the Monte Carlo method can be used as a recommendation to predict the level of passenger spikes and also help in improving services to prospective passengers of PT. Tri Arga Travel.